2007
DOI: 10.1175/jas3820.1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Eddy-Driven Low-Frequency Dipole Modes. Part II: Free Mode Characteristics of NAO and Diagnostic Study

Abstract: Through calculating the scatter diagrams of the streamfunction ( P or T ) versus potential vorticity (PV) (q P or q T ), where P and T are the planetary-scale streamfunction and total streamfunction, respectively, and using a weakly nonlinear NAO model proposed in Part I of this paper, it is suggested that negative-and positive-phase NAO events may approximately correspond to free modes even though driven by synopticscale eddies. In a planetary-scale field, the q P ( P ) scatter diagram of an NAO event exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 23 publications
(56 reference statements)
4
28
0
Order By: Relevance
“…In this paper, to theoretically explain the north-south shift of the zonal mean wind anomalies associated with the NAO, we will still use an equivalent barotropic vorticity equation with bottom topography as in Luo (2005) in that the NAO has generally an equivalent barotropic structure in the troposphere (Wallace 2000;Vallis et al 2004;Gerber and Vallis 2005;Wittman et al 2005).…”
Section: Analytical Solutions Of Planetary-and Synoptic-scale Fields mentioning
confidence: 99%
See 4 more Smart Citations
“…In this paper, to theoretically explain the north-south shift of the zonal mean wind anomalies associated with the NAO, we will still use an equivalent barotropic vorticity equation with bottom topography as in Luo (2005) in that the NAO has generally an equivalent barotropic structure in the troposphere (Wallace 2000;Vallis et al 2004;Gerber and Vallis 2005;Wittman et al 2005).…”
Section: Analytical Solutions Of Planetary-and Synoptic-scale Fields mentioning
confidence: 99%
“…In a recent theoretical study by Luo et al (2007a), the phase of the eddy-driven NAO is found to depend upon the spatial structures of preexisting planetary-and synoptic-scale waves, implying that the NAO is indeed a nonlinear initial-value problem (Benedict et al 2004). However, the analytical solutions in this model cannot be directly used to interpret the north-south shift of the westerly jet associated with the phase of NAO although synoptic-scale eddies are found to maintain the zonal mean wind anomalies through exciting the NAO anomaly.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations